Nutritional status and perinatal characteristics of children with autism spectrum disorder (Research, Society and Development, 2022)
Introduction: recent data show that exposure to certain conditions during pregnancy may result in the development of autism. Objective: to evaluate the nutritional status and perinatal characteristics of children with autism spectrum disorder. Methodology: A descriptive and cross-sectional study was conducted in 2021, with 47 children of both genders, with autism, in different degrees of severity, aged ≤8 years, treated at a reference center in the city of Belém, Pará. After the legal guardians signed the free and informed consent form, weight and height were collected to evaluate the nutritional status and later a form was applied to collect data on age, sex and perinatal characteristics of the children. Results: There was a significant prevalence of male gender (89.4%; n=42) and children 5 years old (40.4%; n=19). About the perinatal characteristics, it was observed that the significant majority (p